Comparison between modern western architettura and Islamic Arabic architectureâ€œimitation and differencesâ€ - Bassam Abu Awwad, Dr. (International Journal of Engineering and Technology, 2019)
Architecture research is the mother of all art, representing the civilization of the population in every part; it is influenced by religion, politics and economy which are the foundations of its art over the centuries. Research on the architecture of Arab-Islamic civilization should be discussed primarily through generality principles of architecture, and the values granted and realized by the human sense of existing or loaded aesthetic qualities in the form of architecture, general. Then continue to look for the champions reached by the particular civilization. The position of the research in architecture, however, serves as a jump to conclusions before appropriate extracts are reached and not submitted to a rigorous examination. The research is a comparison between Arab-Islamic civilization and other civilizations that have created values for completeness. To facilitate this comparison, the research choose the civilization closest to Arab Islamic civilization in terms of the vision of existence and its proximity to the site, which is Western civilization. â€¢ Two civilizations have had so many shared values, thanks to the cultural and architectural imitations due to the proximity and commercial exchange between the East and the West, creating a mixed architecture, since the twelfth century. Christian civilization has made many moves, including multiple versions of completeness and various aesthetic values. While the Arab Islamic civilization reached an aesthetic value in its emergency phase, in the eighth century, and stopped in the twelfth century. Since the beginning of the nineteenth century, the Islamic Arab world has been aware of the entry of Napoleon into Egypt, since it addresses aesthetic values based on the knowledge of structural and aesthetic technology that has had no role in its creation:1)Â Â Â Â Â Since man has found the art, caves (Lascaux) and (Altmira) attest the masterpieces of art in which human Zain, and for thousands of years, Mgairh, who was based in his home, and live this, consisting of colored fees for extinct ornamental animals, skill and realism, confirm that Art is a means of communication that preceded language and literature in the human life.2)Â Â Â Â Â When civilization progressed, the dwelling became the space absorbed the skills and talent of artists, discovered in the homes such as Valley Alntov (Palestine), or in Amartibt (Syria), which dates back to the seventh millennium BC, were decorated with colorful patterns.3)Â Â Â Â Â The architecture by itself, soon of became the exterior appearance and its mass and its divisions, something of three-dimensional art, must be a creative work, and thought of engineering; however area that houses all the types of continuous plastic art architecture, shooting, or sculpture. This was reflected strongly in Islamic architecture, and we saw that in the Umayyad palaces, which were characterized by colorful or stained sculptures, and graphically mosaics and Altleuenah, which still freshly raised in the palaces of Heer and Mushatta Palace, and Amra bath.4)Â Â Â Â Â If the art collages to be separated from architecture in order to solve unmovable objects, such as manuscripts, pots and accessories architecture and furniture, the methods have not changed much, they can either be simulated realistically, or be abstract decorative, the diversity of methods and interpretations has changed even today.Â Â Â